Indonesia in the South China Sea: Foreign Policy and Regional Order - I Gede Wahyu Wicaksana (Global Strategis, 2019)
This paper looks at how Indonesia contributes to the creation of a relatively peaceful and stable Southeast Asian region after the Cold War. It examines Jakarta’s diplomacy in the South China Sea, and explains its implications for the making of the regional order. The argument is that Indonesia’s impact on regional security has been apparent in its attention to the improvement of rule-based interaction among states in the region. However, recent developments have demonstrated that Indonesia’s initiatives, formulated in the Indo-Pacific Cooperation Concept, are unsuccessful due to the lack of support from other ASEAN states. This paper shows that great powers politics in the troubled waters has hindered the advancement of Indonesian’s order-driven policy.  Keywords: ASEAN, Indonesia, Indo-Pacific Concept, Regional Order, South China Sea.  Tulisan ini membahas kontribusi Indonesia dalam menciptakan Kawasan Asia Tenggara yang relatif damai dan stabil setelah Perang Dingin berakhir. Fokus bahasan pada diplomasi yang dilakukan dalam meresolusi konflik Laut China Selatan. Penulis berargumen dampak keterlibatan Indonesia terlihat dari upaya untuk mendorong interaksi yang berdasarkan pada norma dan aturan bersama antar-negara Asia Tetangga. Namun, perkembangan terkini menunjukkan inisiatif Jakarta, khususnya Konsep Kerja Sama Indo-Pasifik, kurang berhasil karena kurang mendapat dukungan anggota ASEAN. Paper ini juga membuktikan bahwa politik kekuatan menjadi hambatan bagi implementasi kebijakan luar negeri Indonesia dalam kasus Laut China Selatan. Kata-kata kunci: ASEAN, Indonesia, Indo-Pasifik, Laut China Selatan, Tatanan Kawasan.